(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The present study was executed to explore in vivo antinociceptive, antipyretic and neuropharmacological activities of different leaf extracts of Citrus assamensis in Swiss albino mice. C. assamensis leaf extract displayed marked dose dependent antinociceptive potential in the five pain models. All leaf extracts except chloroform (200 mg/kg body weight) extract, produced significant (**p<0.01, ***p<0.001) antinociception against thermal induced pain stimuli in mice at various time points of post treatment in hot plate study compared to the control group. In acetic acid induced writhing assay, methanol (100 mg/kg body weight) and chloroform (200 mg/kg body weight) extracts showed significant (*p<0.01) result. In tail immersion test, basal reaction time was found significant (*p<0.01) in case of ethanol (100 mg/kg body weight) and chloroform (200 mg/kg body weight) extracts compared against control. Both the doses of all the extracts exhibited significant (***p<0.001) activity in formalin induced paw licking as well as percent inhibition of glutamate induced writhing study. Both the doses of methanol and ethanol extracts showed significant (*p<0.05) results in decreasing in rectal temperature after 1 hr. Higher doses of all the extracts showed significant (*p<0.05) decrease in duration of immobility in foreed swimming test (FST). The higher dose of ethanol extract (200 mg/kg body weight) significantly (*p<0.05) decreased the rate of movement with time in open field test. The test samples displayed marked antinociceptive potential in all the test procedures and also displayed marked antipyretic and neuropharmacological activities at different test doses. Bangladesh Pharmaceutical Journal 21(2): 87-95, 2018